Can science and technology save China? - Greenhalgh, Susan; Zhang, Li, 1965 May- (Cornell University Press, 2020)
"This study of the intimate connections between science and society in China shows that science and technology, far from saving China, as the country's leaders promise, are producing unanticipated, often deeply disturbing effects"--